2020
DOI: 10.3390/jmmp4040106
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Quality Gates in Manufacturing Systems: Framework, Implementation and Potential

Abstract: Manufacturing companies are exposed to increased complexity and competition. To stay competitive, companies need to minimize the total cost of quality while ensuring high transparency about process–product relationships within the manufacturing system. In this context, the development of technologies such as advanced analytics and cyber physical production systems offer a promising approach. This paper discusses and defines essential elements of virtual quality gates in the context of manufacturing systems. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In this context, Hürkamp et al show the applicability and potentials of fast and accurate data-driven surrogates of FEM simulations for the design of process chains [24] and as virtual quality gates [17]. In addition, Filz et al [7] discuss the design and potentials of virtual quality gates for future manufacturing, considering FEM surrogate modeling as a promising approach.…”
Section: Integrated Computational Product and Production Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Hürkamp et al show the applicability and potentials of fast and accurate data-driven surrogates of FEM simulations for the design of process chains [24] and as virtual quality gates [17]. In addition, Filz et al [7] discuss the design and potentials of virtual quality gates for future manufacturing, considering FEM surrogate modeling as a promising approach.…”
Section: Integrated Computational Product and Production Engineeringmentioning
confidence: 99%
“…In this context, digital twins are even able to implement a databased control of the production [5,6]. Several approaches for (virtual) quality gates in manufacturing systems based on process and machine data can be found for single processes, but very sparse approaches for process chains [7]. If process chains are considered, the data-driven models widely draw on product data such as intermediate and final product properties.…”
Section: Introductionmentioning
confidence: 99%
“…Filz, et al [19], provide a comprehensive overview of virtual quality gates in manufacturing systems. This method supports the reduction of the total cost of quality while ensuring high transparency about process-product relationships in production.…”
Section: Quality Managementmentioning
confidence: 99%
“…This can only be achieved by understanding the dynamics and interdependencies within the process chain. Furthermore, the "context of product quality, transparency and understanding of process-product relationships, which describe interactions and the impact of the manufacturing processes on the resulting intermediate product features and vice versa, are of great importance" [19]. The concept of quality gates is therefore to systematically divide the manufacturing chain into different quality-relevant decision points.…”
Section: Quality Managementmentioning
confidence: 99%
“…Filz et al [5] introduced the CPPS concept of virtual quality gates that allow for the data-based prediction of product quality properties as not only the basis for improved planning and operation of production processes, but also process chains. Based on an overall framework with different design options, several case studies were shown to demonstrate applicability and potential.…”
mentioning
confidence: 99%